Energy Parameters of Interfacial Layers in Composite Systems: Graphene – (Si, Cu, Fe, Co, Au, Ag, Al, Ru, Hf, Pb) and Semiconductor (Si,Ge) – (Fe, Co, Cu, Al, Au, Cr, W, Pb) - B.P. Koman; V.M. Yuzevich (Журнал нано- та електронної фізики)
On the basis of the non-equilibrium thermodynamics relations and the surface physics phenomena we calculate adhesion and energy parameters to characterize the interfacial interactions in graphene – (Si, Cu, Fe, Co, Au, Ag, Al, Ru, Hf, Pb) and semiconductor (Si, Ge) – (Fe, Co, Cu, Al, Au, Cr, W, Pb) systems. We analyze trends of the interfacial energy, interfacial tension, work of adhesion and the energy of adhesive bonds on the contacting element’s atomic number in the periodic table and on the electronegativity difference of interacting elements. Thus, this work provides theoretical basis for the development of new composite materials.